2019
DOI: 10.1007/s11769-019-1060-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Mapping Cropping Patterns on Smallholder Scale Croplands Using Sentinel-1 SAR Data

Abstract: It is of paramount importance to have sustainable agriculture since agriculture is the backbone of many nations' economic development. Majority of agricultural professionals rarely capture the cropping patterns necessary to promote Good Agricultural Practises. Objective of this research is to explore the potential of mapping cropping patterns occurring on different field parcels on small-scale farmlands in Zimbabwe. The first study location under investigation are the International Maize and Wheat Improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 30 publications
(42 reference statements)
1
19
0
Order By: Relevance
“…These results are similar to those of Abubakar et al [53], who observed an OA of 78.9% when mapping smallholder maize using Sentinel-1 data by applying SVM. However, Useya and Chen [54] reported an OA of 46% with RF and 40% with K-means classification when mapping smallholder maize farms and other crops with Sentinel-1 single-date data. The poor performance of the Sentinel-1 C-band data could be because of its shorter wavelength, which decreases canopy penetration in comparison to L-band SAR, which has a longer wavelength [55,56].…”
Section: Discussionmentioning
confidence: 98%
“…These results are similar to those of Abubakar et al [53], who observed an OA of 78.9% when mapping smallholder maize using Sentinel-1 data by applying SVM. However, Useya and Chen [54] reported an OA of 46% with RF and 40% with K-means classification when mapping smallholder maize farms and other crops with Sentinel-1 single-date data. The poor performance of the Sentinel-1 C-band data could be because of its shorter wavelength, which decreases canopy penetration in comparison to L-band SAR, which has a longer wavelength [55,56].…”
Section: Discussionmentioning
confidence: 98%
“…Sentinel-2 was chosen for its high spatial resolution and public availability, and prior work has shown that optical features can be used to distinguish crop types [14,18,27,41]. Sentinel-2A was first launched by the European Space Agency (ESA) in June 2015 as part of the European Union's Copernicus Programme for Earth observation, and captures high-resolution (10-60 m) optical imagery to serve a wide range of scientific applications on land and in coastal waters.…”
Section: Sentinel-2 Time Seriesmentioning
confidence: 99%
“…Yet, to date, relatively little work has been carried out to map crop types in smallholder systems compared to other agricultural characteristics, such as cropped area and yield. The work that does exist to map smallholder crop types using readily available imagery has largely focused on using Sentinel 1 and 2 [9,[12][13][14]], yet it is likely that micro-satellite data could improve classification accuracies given their higher spatial resolution, which reduces the effect of mixed pixels at field edges [15]. To the best of our knowledge, only two studies have examined the benefits that Planet micro-satellite data provide when mapping smallholder crop types, and these two studies were conducted in Africa [16,17].…”
Section: Introductionmentioning
confidence: 99%